#Changethedate: Advocacy as an on-line and decolonising occupation. Issue 3 (2nd July 2020) - Ryan, Ashleigh; Gilroy, John; Gibson, Chontel
ABSTRACT: Introduction: Advocacy promotes equity and social justice and, in Australia, this involves decolonising colonial hegemony and dominant practices. Aboriginal and Torres Strait Islander people use the Change the Date campaign as one mechanism to raise awareness of ongoing inequities resulting from colonisation. Although the literature highlights Aboriginal and Torres Strait Islander people's advocacy, it does not capture how Aboriginal and Torres Strait Islander people's advocacy operates within the context of 'occupations.' This research aimed to explore how Aboriginal and Torres Strait Islander people experience and express advocacy as an occupation, via an on-line platform. Method: Indigenous Standpoint Theory and cultural interface provided a methodological framework, privileging Indigenous knowledge and culture and underpinning the decolonising documentary analysis. Data were collected from eight Facebook pages managed by Aboriginal and Torres Strait Islander people and analysed using thematic analysis. Results: Three themes describing Aboriginal and Torres Strait Islander people's experience and expressions of advocacy emerged. The first theme focused on the Australian context and identity, where racism was the common thread. The second theme related to the protective and risk factors of social and emotional well-being. Finally, the third theme related to advocacy as an occupation, highlighting how this occupation occurred via Facebook. Conclusion: Aboriginal and Torres Strait Islander people continue to survive the harsh environments created by Australian contexts. Aboriginal and Torres Strait Islander people's advocacy illustrated how decolonising occupations are essential to address systemic issues, and additionally provided an opportunity to participate in cultural occupations.